Perspectives of Social Service Development in Connection with the Adoption of the Federal Statute "On the Fundamentals of Social Service of the RF Citizens" - M. Yu. Dityatkovsky (Сибирское юридическое обозрение)
The article deals with the analysis of the basic provisions of the Federal statute "On the fundamentals of social service of the RF citizens" aimed at social service reforming in the Russian Federation.